2009
DOI: 10.1016/j.janxdis.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life impairment in generalized anxiety disorder, social phobia, and panic disorder

Abstract: Interest in the assessment of quality of life in the anxiety disorders is growing. The present study examined quality of life impairments in individuals with Generalized Anxiety Disorder (GAD), Social Phobia, and Panic Disorder. Results showed that individuals with these disorders reported less satisfaction with their quality of life than non-anxious adults in the community. However, the degree of quality of life impairment is similar across these three disorders. Additionally, comorbid depression, but not anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(156 citation statements)
references
References 23 publications
6
144
1
5
Order By: Relevance
“…McKnight et al 10 showed that anxiety disorders such as agoraphobia and generalized anxiety disorder (GAD) have a stronger association with social isolation than social phobia (SP). This is in contrast to findings that GAD, SP, and panic disorder (PD) did not differ in the amount of social impairment 11 or to the finding that PD was most impaired in social functioning in comparison to other anxiety disorders 12.…”
Section: Introductioncontrasting
confidence: 99%
“…McKnight et al 10 showed that anxiety disorders such as agoraphobia and generalized anxiety disorder (GAD) have a stronger association with social isolation than social phobia (SP). This is in contrast to findings that GAD, SP, and panic disorder (PD) did not differ in the amount of social impairment 11 or to the finding that PD was most impaired in social functioning in comparison to other anxiety disorders 12.…”
Section: Introductioncontrasting
confidence: 99%
“…No transtorno de pĂąnico, fobia social e transtorno de ansiedade generalizada, problemas psicossociais e altos nĂ­veis de ansiedade podem comprometer a qualidade de vida 50,51 . As comorbidades entre transtornos de ansiedade e de humor sĂŁo comuns e apresentam maior prejuĂ­zo Ă  qualidade de vida 52,53 .…”
Section: Discussionunclassified
“…Generalized anxiety disorder seems to be one of the most frequent diagnoses 5,6 and its chronic course 7 and negative impact on quality of life is recognized 8 . Some studies using epidemiologic samples indicate that this specific disorder and alcohol or drug use co-occur and are associated 9,10 .…”
Section: Introductionmentioning
confidence: 99%